2008
DOI: 10.1152/ajplung.00025.2008
|View full text |Cite
|
Sign up to set email alerts
|

Multiple TLRs activate EGFR via a signaling cascade to produce innate immune responses in airway epithelium

Abstract: Toll-like receptors (TLRs) are critical for the recognition of inhaled pathogens that deposit on the airway epithelial surface. The epithelial response to pathogens includes signaling cascades that activate the EGF receptor (EGFR). We hypothesized that TLRs communicate with EGFR via epithelial signaling to produce certain innate immune responses. Airway epithelium expresses the highest levels of TLR2, TLR3, TLR5, and TLR6, and here we found that ligands for these TLRs increased IL-8 and VEGF production in norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
191
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(206 citation statements)
references
References 36 publications
(45 reference statements)
14
191
1
Order By: Relevance
“…DUOX1-dependent EGFR activation can promote airway epithelial production of the neutrophil chemokine IL-8 (27,30). Analysis of BAL fluids from HDM-challenged wild-type mice indicated marked and DUOX1-dependent increases of the mouse functional IL-8 homolog CXCL1, consistent with the observed DUOX1-dependent neutrophilia in this model ( Figure 4A).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…DUOX1-dependent EGFR activation can promote airway epithelial production of the neutrophil chemokine IL-8 (27,30). Analysis of BAL fluids from HDM-challenged wild-type mice indicated marked and DUOX1-dependent increases of the mouse functional IL-8 homolog CXCL1, consistent with the observed DUOX1-dependent neutrophilia in this model ( Figure 4A).…”
Section: Resultssupporting
confidence: 76%
“…An additional consequence of IL-33-mediated ILC2 recruitment and activation is the production of AREG, which forms an essential component of EGFR-mediated epithelial repair responses in the context of parasite/helminth infection (47) but may also contribute to sustained EGFR activation in chronic asthma. Moreover, DUOX1 contributes to EGFR activation not only by promoting EGFR ligand activation, as previously reported (23,27), but also by promoting ligand-induced activation of EGFR phosphorylation by direct cysteine oxidation within EGFR. Although chronic epithelial alterations during allergic asthma are commonly attributed to epigenetic changes, potentially involving important asthma-relevant cytokines such as IL-13 (8, 48, 49), our results indicate that such alterations are also mediated by redox-dependent mechanisms due to enhanced expression and activation of DUOX1 and can be attenuated by inhibition of DUOX1.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, the cell type in which EGFR signaling occurs to prevent experimental colitis needs to be identified. Some evidence from in vitro studies using colonic epithelial cell lines suggested the possibility that Toll-like receptor (TLR) signaling might induce expression of EGFR ligands (18)(19)(20)(21). Also, studies using a model of colitis-associated cancer demonstrate that TLR4-dependent tumorigenesis is associated with activation of EGFR signaling (18).…”
mentioning
confidence: 99%
“…Accordingly, EGFR signalling has been suggested as a convergent pathway for regulation of CXCL8 and other immune responses [23]. Recent studies with endogenous and microbial ligands have shown that CXCL8 regulation by EGFR involves transforming growth factor (TGF)-a ectodomain shedding by the metalloprotease tumour necrosis factor-a-converting enzyme (TACE)/ADAM-17 [20,21,24,25]. Whether organic or inorganic PM components regulate CXCL8 through similar mechanisms remains to be elucidated.…”
mentioning
confidence: 99%